Efeito de subdoses de glyphosate sobre a germinação de sementes das cultivares de soja RR e convecional - Melhorança Filho, André Luiz; Pereira, Maria Renata Rocha [UNESP]; Martins, Dagoberto [UNESP] (My University, 2011)
The aim of this work was to evaluate the quality of seeds of two soybean cultivars CD-216 and CD-212RR, under subdoses of glyphosate (1,3; 2,6; 5,3 and 11,5 g e.a.ha -1). The experiments carried out in Laboratory Fisiologoa Plant in the Uniderp, city of Dourados/MS. The experimental design used was in blocks entirely at random, with four repetitions. After soaking, evaluated the following parameters eight days after imbibition: % germination, seedling dry weight, length of root and shoot. Seeds of both cultivars (CD-212RR and CD216) reduce the percentage of germination, with the increasing of glyphosate concentration in soaling, and CD-216 was more sensible to herbicide.
Effect of subdoses glyphosate on the germination of seeds of soybean cultivars RR and conventional
Keywords: Glycine max; Glyphosate; Herbicide; Transgenic